Vulvar squamous intraepithelial neoplasia epithelial thickness in hairy and non-hairy sites: a single center experience from China - Xiao, Jingjing; Chen, Ziren; Xiao, Yinping; Sui, Long; Wang, Chao; Cong, Qing (Frontiers in Oncology, 2023)
Introduction A large-sample study focusing on VIN lesions of a more precise thickness is needed to help guide clinical treatment. This study aimed to investigate the depth of vulvar intraepithelial neoplasia (VIN) and involved skin appendages to provide evidence for laser surgery. Methods The study retrospectively enrolled and analyzed the clinical characteristics of VIN patients in the obstetrics and gynecology department of a university hospital between January 1, 2019 and December 30, 2021. The study further explored the thickness of epithelium and skin appendages of 285 women with low-grade VIN (VIN1) and 285 women with high-grade VIN (VIN2/3). Results The study included 1,139 (80%) VIN1 and 335 (20%) VIN2/3 cases. The VIN1 and VIN2/3 groups showed a significant difference in human papillomavirus infection (P<0.01) but not in cytology (P = 0.499). Most (89.90%, 1,325) cases occurred in one area of the vulva, whereas 10.11% were multifocal. VIN commonly occurred on the posterior fourchette (76.85%), labia majora (11.61%), and labia minora (9.92%). The VIN2/3 group reported a significantly higher positive rate for concurrent cervical and vaginal intraepithelial neoplasia (160 of 285) than the VIN1 group (321 of 953) (P=0.000). The involved epithelial thicknesses in VIN2/3 and VIN1 were 0.69 ± 0.44 and 0.49 ± 0.23 mm, respectively, both of which were greater than the corresponding noninvolved epithelial thickness (0.31 ± 0.19 and 0.32 ± 0.10 mm, P<0.001 and P<0.001, respectively). In cases of appendage involvement, the VIN thickness was 1.98 ± 0.64 mm. Conclusions VIN thickness was generally ≤1 mm for the superficial lesions in non-hairy areas. However, for lesions extending onto hairy areas, the thickness was approximately 3 mm, leading to the destruction of involved skin appendages.